Adaptive control strategies for enhancing the performance and stability of renewable energy systems - Kunumalla, Sreedevi; Rajababu, Durgam; Sudhakar, A. V. V. (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
The comparison done in this paper uses two control strategies for a solar-fed three-phase inverter, one with standard sinusoidal pulse width modulation (SPWM) and the other with unified space vector PWM (USPWM), equipped with adaptive voltage control (AVC) and a load current observer (LCO). A photovoltaic (PV) source feeds into a controlled DC link, which in turn supplies a DC voltage to the inverter powering an RL load. From the simulation, it is clear that although SPWM meets the output standards, it has increased total harmonic distortion (THD) and slower transient response. Alternatively, using USPWM control decreased THD to 3.01% and made the system respond in 11 ms, compared to 22 ms before. The new method provides better efficiency and better power quality when used with dynamic loads.